-2=6(x+3)-2x

Simple and best practice solution for -2=6(x+3)-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=6(x+3)-2x equation:


Simplifying
-2 = 6(x + 3) + -2x

Reorder the terms:
-2 = 6(3 + x) + -2x
-2 = (3 * 6 + x * 6) + -2x
-2 = (18 + 6x) + -2x

Combine like terms: 6x + -2x = 4x
-2 = 18 + 4x

Solving
-2 = 18 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-2 + -4x = 18 + 4x + -4x

Combine like terms: 4x + -4x = 0
-2 + -4x = 18 + 0
-2 + -4x = 18

Add '2' to each side of the equation.
-2 + 2 + -4x = 18 + 2

Combine like terms: -2 + 2 = 0
0 + -4x = 18 + 2
-4x = 18 + 2

Combine like terms: 18 + 2 = 20
-4x = 20

Divide each side by '-4'.
x = -5

Simplifying
x = -5

See similar equations:

| 284=-66a | | 4x^2+2x+1=o | | 2x-2=11-4x | | (X-5)^5/3-73=170 | | 10^6/10^2= | | n+1.2=7.4 | | Tan(28)=x/32 | | 4c-39=43c-78 | | 3(7+3x)=30 | | 5/3m=5/9 | | (q-12)(6q+1)=0 | | 150=x+1.5x | | 2/7×7/2x=424×2/7 | | -5(5y-2)-y=-2(y-3) | | 8-3x+13=15 | | 5x+3.9=3x+27 | | 20=4x-5y | | S=Y-(150+0.60Y) | | 0.0l(500-70x)=3.2x+300 | | -4m+8=-12 | | 5(3x+12)-12x= | | 5.5x+19=6.75x+9 | | 30-x=2x+3 | | 30x=12 | | 16+8x=x^2 | | t+68=7t-58 | | 4x-5+2(x-3)=12x+5 | | 6-4y=14 | | 7x-25=-63 | | 3p-28=180 | | 1+1.5ln(x+1)=10 | | 8(9+8x)+12= |

Equations solver categories